Efek Mediasi Kompetensi Atas Pengaruh Proses Seleksi Pegawai Terhadap Persepsi Kinerja Pegawai - Tigor Sitorus; Ali Ghozi (Universitas Bunda Mulia, 2016)
This study aims to extend a model research empiric the influence of process selection of employee to employee performance mediated by Competency of employee. Population ini this study are employees at Inspectorate General of Ministry of Religion Affair. The sampel was used in this study are 112 respondents by sensus method. Data analysis was conducted by using Structural Equation Modeling (SEM) using AMOS 21.0 (Analysis of Moment Structures). The SEM analysis result has fulfilled Goodness of Fit Index Criteria, and has a high loading factor. The result shows that; (1) Process selection of employee has positive and significantly influence on the Competency of employee, (2) Process selection of employee has negative and significantly influence on the employee performance, (3) Competency of employee has positive and significantly influence on the employee performance. Therefore mediated effect of Competency of employee greater than direct effect process selection of employee to employee performance.Keywords: Selection, Competency, Performance, Employee